Netflix Documentary Series in Spain. Challenging the Classical Seriality Norms - Naranjo, Adrià; Nevado, Ignacio; Fernández-Ramírez, Laura (Estudios sobre el Mensaje Periodístico, 2023)
This research analyzes the impact of Netflix’s all-at-once premiere on the dynamics of seriality. The digitalization of television has profoundly modified the medium, and the binge watching, and the abandonment of the weekly premiere have completely changed the consumption and the creation of fictions. To address this issue, we focus on the documentary series produced by the company in Spain: Examen de conciencia (2019), El caso Alcàsser (2019), La Línea: La sombra del narco (2020) and Nevenka (2021). The main consequences generated by the elimination of the wait between episodes make the episodic plots overflow the chapter and serial storylines do not follow patterns linked to speculation. Consequently, the episodes lose their formal unity or, directly, seriality is abandoned as a narrative model. This paradigm reinforces the idea that, by modifying the distribution methodology, the syntactic characteristics of the products are also altered.